Accessibility and connectivity of the road network in the State of Bouira - Amir, Amar; ALKAMA, Djamal; BENMISSI, Ahcene (Journal of Human Sciences, 2020)
The wilaya of Bouira presents a very vast territory inserted between the mountains of Djurdjura and that of the Bibans including flat areas in the center. This region has an important road network composed of different roads and paths. Based on the theory of graphs (topological graphs) and geographical indices, we highlight the main characteristics of the road network of Bouira, which contains 56% of the connected roads in relation to its maximum capacity. The Shimbel indices, calculated from the matrix of the shortest paths, enabled us to identify four accessibility zones (high, medium, low and very low accessibility). The importance of the Bouira territory and the degree of connectivity revealed by the Gama index (0.65). Showed us that part of this territory is landlocked. This article presents an awareness of the need to improve accessibility to Bouira and to ensure the opening up of the regions concerned.